Urothelial carcinoma in a mule - Valim, A. C. [UNESP]; Costa, A. M.D. [UNESP]; Quitzan, J. G. [UNESP]; Borges, A. S. [UNESP]; Oliveira-Filho, J. P. [UNESP]; Amorim, R. M. [UNESP]; Andrade, D. G.A. [UNESP] (Elsevier, 2024)
Equine bladder neoplasms are rare. This report aimed to describe the clinical signs and treatment of urothelial carcinoma (UC) in a mule. Cystoscopy of a 20-year-old female mule with a one-week history of hematuria and anemia revealed vascular congestion in the mucosa and an intraluminal, pedunculated mass in the dorsal bladder region. Histopathological examination revealed UC. Initial therapy consisted of four weekly cystoscopic guided injections of fluorouracil. At the fourth chemotherapy session, a paler and more friable tumor mass was observed. Consequently, we opted to surgically remove it during cystoscopy. Following mass excision, patient comfort, gross appearance of urine, and the hematocrit returned to normal. Repeat cystoscopy examinations revealed no gross appearance of tumor recurrence 18 months after treatment. Bladder neoplasms clinically resemble urolithiasis and cystitis and should be considered a differential diagnosis in cases of anemia and hematuria.
Keywords: Equids; Fluorouracil; Transitional cell carcinoma; Urinary bladder; Urinary neoplasia